Resistance element weld-bonding and resistance spot weld-bonding of Mg alloy/austenitic stainless steel - Manladan, Sunusi Marwana; Zhang, Y.; Ramesh, Singh; Cai, Yang Chuan; Luo, Zhen; Ao, Sansan; Arslan, A. (Elsevier, 2019)
Mg alloy/austenitic stainless steel (ASS) joints were produced by resistance element weld-bonding (REWB) and resistance spot weld-bonding (RSWB) techniques. Both joints consisted of two zones, namely, the adhesive zone and weld zone. The weld zone of the REWB joints was formed through a metallurgical reaction between the rivet and ASS. The microstructure of the fusion zone consisted of austenite and intercrystalline delta ferrite. The weld zone of the RSWB joints was formed via welding-brazing mechanism (involving molten Mg alloy and solid ASS), and the nugget was formed in the Mg alloy. The nugget microstructure consisted of fine columnar dendritic structure. Digital image correlation (DIC) analysis was used to study the deformation behavior and strain evolution in the loading direction during lap-shear test. The REWB and RSWB joints experienced lower degree of out-of-plane displacement, sustained higher peak load, and exhibited higher strain to failure than their conventional counterparts. However, the REWB joints exhibited superior lap-shear performance, with high energy absorption and favorable failure mode (pull out failure in the ASS sheet). Upon the failure of the adhesive zone at peak load, the load was sustained by the weld, and the final failure occurred via pullout mode in the ASS. The RSWB joints failed in a sudden manner, mainly by cohesive failure in the adhesive zone and Mg alloy nugget/ASS interface failure in the weld zone. © 2019 The Society of Manufacturing Engineers